2023
DOI: 10.29303/jipp.v8i1.1193
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Power-Point Media on Student Learning Outcomes Fifth Grade students at SDIT Adzkia II Padang

Abstract: The problem in this study is the low student learning outcomes in science learning. The difficulty can be seen from the lack of use of media in learning activities. Based on this, the researchers took the initiative to test a teaching aid media to improve student learning outcomes. The design of this study uses a Quasi Experimental Design with a design form Nonequivalent Control Group Design. The population in this study were fifth grade students at SDIT Adzkia II Padang, for the 2022/2023 academic year, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…In qualitative research, the primary consideration in data collection is the selection of informants. The informant determination technique in this study was taken using a non-probability sampling technique which is a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as a sample [15]. One type of non-probability sampling technique used is purposive sampling, namely sampling with certain considerations [16].…”
Section: Methodsmentioning
confidence: 99%
“…In qualitative research, the primary consideration in data collection is the selection of informants. The informant determination technique in this study was taken using a non-probability sampling technique which is a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as a sample [15]. One type of non-probability sampling technique used is purposive sampling, namely sampling with certain considerations [16].…”
Section: Methodsmentioning
confidence: 99%
“…The initial stage is analysis, in the analysis stage observations are made at school and analysis of the curriculum and analysis of students, by making initial observations at SDN 03 Simpang Haru by looking at learning and school facilities. At the analysis stage, researchers found that students needed interesting learning, namely using interactive PowerPoint learning media which could help students be more active in appropriate learning activities (Alfiyandri et al, 2023). After that, an analysis is carried out according to the curriculum at school with the material that will be produced through the media.…”
Section: Analysis Stagementioning
confidence: 99%